1999
DOI: 10.1046/j.1462-5822.1999.00014.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Shigella flexneri-induced transepithelial migration of polymorphonuclear leucocytes by cadaverine

Abstract: SummaryDysentery caused by Shigella species is characterized by in®ltration of polymorphonuclear leucocytes (PMNs) into the colonic mucosa. Shigella spp. evolved into pathogens by the acquisition of virulence genes and by the deletion of`antivirulence' genes detrimental to its pathogenic lifestyle. An example is cadA (encoding lysine decarboxylase), which is uniformly absent in Shigella spp., whereas it is present in nearly all isolates of the closely related non-pathogen Escherichia coli. Here, using monolaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 41 publications
3
40
0
Order By: Relevance
“…Despite the beneficial role that the CadBAC lysine-dependent acid resistance system might have in the survival of enteric organisms in the intestine, cumulative evidence indicates that the absence of these genes, due to deletions or insertional mutagenesis, in some members of the family Enterobacteriaceae results in an enhancement of their virulence phenotype (31). For example, it is well documented that attenuation of virulence phenotypes in Shigella flexneri 2a has been linked to expression of LDC and, specifically, to the production of cadaverine (7,18,19). These studies demonstrated for the first time that the cadA gene acts as an antivirulence gene for Shigella.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the beneficial role that the CadBAC lysine-dependent acid resistance system might have in the survival of enteric organisms in the intestine, cumulative evidence indicates that the absence of these genes, due to deletions or insertional mutagenesis, in some members of the family Enterobacteriaceae results in an enhancement of their virulence phenotype (31). For example, it is well documented that attenuation of virulence phenotypes in Shigella flexneri 2a has been linked to expression of LDC and, specifically, to the production of cadaverine (7,18,19). These studies demonstrated for the first time that the cadA gene acts as an antivirulence gene for Shigella.…”
Section: Discussionmentioning
confidence: 99%
“…It is not known whether their O111:H Ϫ isolate lacked the LDC system. The role of the cad operon in virulence expression and as an inducible system that responds to environmental factors was first elucidated by Maurelli et al, who found that introduction of cadA in Shigella flexneri 2a causes attenuation of its virulence and inhibition of enterotoxin production (32) and showed that cadaverine had an effect on the migration of polymorphonuclear leukocytes across the intestinal epithelial monolayers as well as inducing compartmentalization of Shigella species to the phagolysosome (18,33). Furthermore, they revealed that the lack of LDC activity in Shigella strains is due to a large chromosomal deletion up to 90 kb in the vicinity of the cadA gene (16) and proposed that the presence of "black holes" is a mechanism which provides an evolutionary advantage enabling S. flexneri to increase its pathogenic potential in host tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The cadA gene encodes the lysine decarboxylase enzyme, responsible for metabolizing lysine, and these investigators found that loss to lysine decarboxylase (LDC) activity was due to a large chromosomal deletion comprising the cadA region (16). Further studies indicated that introduction of cadA in S. flexneri affects the activity of two enterotoxins and the presence of the byproduct cadaverine, generated from the decarboxylation of lysine, caused attenuation in S. flexneri virulence (18,33).…”
mentioning
confidence: 99%
“…One hundred microliters of a stationary-phase culture was used to inoculate 10 ml of TSB, and the bacteria were grown in a shaking incubator for approximately 2 h at 37°C to the mid-exponential phase (optical density at 600 nm of 0.30). Trypticase soy agar is TSB containing 15 g of Bacto agar per liter (Difco Laboratories) (32,33).…”
Section: Methodsmentioning
confidence: 99%